Distributed generation impact evaluation using a multi-objective tabu search - Maciel, R. S. [UNESP]; Padilha-Feltrin, A. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2009)
Distribution networks paradigm is changing currently requiring improved methodologies and tools for network analysis and planning. A relevant issue is analyzing the impact of the Distributed Generation penetration in passive networks considering different operation scenarios. Studying DG optimal siting and sizing the planner can identify the network behavior in presence of DG. Many approaches for the optimal DG allocation problem successfully used multi-objective optimization techniques. So this paper contributes to the fundamental stage of multi-objective optimization of finding the Pareto optimal solutions set. It is proposed the application of a Multi-objective Tabu Search and it was verified a better performance comparing to the NSGA-II method. © 2009 IEEE.
Keywords: Distributed generation; Medium voltage distribution networks; Multiobjective optimization; Optimal allocation; Tabu search; Allocation problems; Distributed Generation; Distribution network; Impact evaluation; Medium-voltage distribution networks; Multi objective; Multi-objective optimization techniques; Network analysis; Network behaviors; NSGA-II; Pareto optimal solutions; Distributed parameter networks; Electric network analysis; Galerkin methods; Intelligent systems; Passive networks; Planning; Voltage distribution measurement; Voltage dividers